Complementary and Alternative Medicine Use in Children with a Developmental Disability and Co-occurring Medical Conditions. (September 2020) - Zisman, Corina R.; Patti, Marisa A; Kalb, Luther G.; Stapp, Emma K.; Van Eck, Kathryn; Volk, Heather; Holingue, Calliope
Highlights: Use of CAMs is common in children with developmental disabilities Co-occurring chronic medical conditions further increases risk of CAM use Research on safety and efficacy of CAMs is critically needed Open doctor-patient communication about CAM use is important given prevalence Abstract: Objective: The primary aim of this study was to evaluate differences in the prevalence of complementary and alternative medicine (CAM) usage among children with and without developmental disabilities (DD). Secondarily, the association between CAM usage and comorbid chronic medical conditions was explored among children with DD. Design: Data come from the 2012 Child Complementary and Alternative Medicine Supplement of the National Health Interview Survey, a nationally representative sample of children in the United States between the ages of 4 and 17 (n = 10, 218).Main outcome measures Multiple logistical regression models provided insight into the relationships between parent-report CAM usage, DD, and chronic medical conditions. Results: Children with developmental disabilities were more likely to use CAMs compared to their typically developing peers (21% vs 16%). Children with DDs and comorbid chronic medical conditions used CAMs at even higher rates (23% vs 18%). Conclusions: Results indicated that children with DD, especially those with a co-occurring chronic medical condition, use CAMs more often that typically developing children. Given scarcity of information on safety and effectiveness, clinical providers need to be alert to which children may be more likely to be exposed to CAMs. Communication between parents and providers needs to include discussion of CAM treatments.